2019
DOI: 10.1088/1612-202x/ab27b9
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Wiener filtering algorithm for processing the signal obtained by the TDLAS method using the synchronous detection technique for the measurement problem of 13CO2 concentration in exhaled air

Abstract: It has been shown clearly that using the synchronous detection technique with the pump current frequency modulation of a tunable diode laser emitting near 2 μm wavelength, combined with the application of the Wiener filtering algorithm for the experimental signal, ensures a two-times improvement in the measurement accuracy for the 13 CO 2 content in exhaled air, and, for the 13 CO 2 and 12 CO 2 concentrations ratio, more than seven times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
1
7
1
Order By: Relevance
“…2. Application of the TDL pump current modulation with subsequent demodulation of the recorded signal using the synchronous detection technique [13][14][15].…”
Section: Application Of Various Digital Methods For Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…2. Application of the TDL pump current modulation with subsequent demodulation of the recorded signal using the synchronous detection technique [13][14][15].…”
Section: Application Of Various Digital Methods For Processingmentioning
confidence: 99%
“…The synchronous detection technique was used in [14]. The experimental signal from the synchronous detector was filtered using the Wiener and Savitsky-Golay filters.…”
Section: Application Of Various Digital Methods For Processingmentioning
confidence: 99%
“…Earlier, this method was used to measure the content of 13 C 16 O 2 (636) in a mixture with 12 C 16 O 2 (626) in exhaled air. Performed studies have shown that one of the most promising ranges for measurements is the region near a wavelength of 2 µm (frequency range: 4860-4880 sm −1 ), which contains a number of absorption curves of these molecules, to a minimum extent overlapping, and the experimental arrangement does not require complex and expensive equipment [18][19][20]. To accurately measure the content of 13 C 16 O 2 and 12 C 16 O 2 in the analyzed mixture, knowledge of the absorption constantvalues and their pressure dependence, since the measurements can be carried out at different pressures, are necessary.…”
Section: Figure 1bmentioning
confidence: 99%
“…Kalman filter [14], wavelet transform [15], moving average [16], Wiener filter [17], and Gabor transform [18] have all been used to address noise suppression problems. Although these five methods reduce the influences of interference fringes on the detected signals, they are computationally intensive and not conducive to practical applications.…”
Section: Introductionmentioning
confidence: 99%